A rapid, easy, and scalable whole blood monocyte CD169 assay for outpatient screening during SARS-CoV-2 outbreak, and potentially other emerging disease outbreaks. (August 2022) - Michel, Moïse; Malergue, Fabrice; Ait Belkacem, Inès; Bourgoin, Pénélope; Morange, Pierre-Emmanuel; Arnoux, Isabelle; Miloud, Tewfik; Million, Matthieu; Tissot-Dupont, Hervé; Mege, Jean-Louis; Vitte, Joana; Busnel, Jean-Marc
Objective: The COVID-19 corona virus disease outbreak is globally challenging health systems and societies. Its diagnosis relies on molecular methods, with drawbacks revealed by mass screening. Upregulation of neutrophil CD64 or monocyte CD169 has been abundantly reported as markers of bacterial or acute viral infection, respectively. We evaluated the sensitivity of an easy, one-step whole blood flow cytometry assay to measure these markers within 10 min, as a potential screening test for COVID-19 patients. Methods: Patients ( n = 177) with confirmed severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection were tested on 10 µL blood and results were compared with reverse transcriptase-quantitative polymerase chain reaction (RT-qPCR). Results: We observed 98% and 100% sensitivity in early-stage ( n = 52) and asymptomatic patients ( n = 9), respectively. Late-stage patients, who presented for a second control RT-qPCR, were negative for both assays in most cases. Conversely, neutrophil CD64 expression was unchanged in 75% of cases, without significant differences between groups. Conclusion: Monocyte CD169 evaluation was highly sensitive for detecting SARS-CoV-2 infection in first-presentation patients; and it returns to basal level upon infection clearance. The potential ease of fingerprick collection, minimal time-to-result, and low cost rank this biomarker measurement as a potential viral disease screening tool, including COVID-19. When the virus prevalence in the tested population is usually low (1%−10%), such an approach could increase the testing capacity 10 to 100-fold, with the same limited molecular testing resources, which could focus on confirmation purposes only.